ANALISIS SIKAP DAN PERILAKU KONSUMEN DALAM PEMBELIAN PRODUK VITAMIN VITACIMIN DI MASA PANDEMI COVID - 19 (STUDI PADA KARYAWAN KOPERASI SERBA USAHA KEMBANG WIJAYA KUSUMA JOMBANG) - NURUL ISNAINI; ITA RAHMAWATI (JURNAL ILMIAH KOHESI, 2021)
This study was conducted with the aim to know the Analysis of Attitudes and Behaviors of Consumers in the Purchase ofVitamin Vitacimin Products in Employees of The Cooperative All-Round Business Kembang Wijaya Kusuma Jombang byusing a sample of 59 respondents with simple random sampling techniques. The results of this study showed a greater fcountvalue than the f-table of 39,826 > 3,162 which means that the variables of consumer attitudes and consumer behaviorsimultaneously positively influenced vitacimin purchasing decisions. And the test results of the t test, t-count variableconsumer attitudes greater than the t-table of 5,028 > 2,003 with the variable meaning of consumer attitudes positivelyinfluenced purchasing decisions. And the result of t-count variable consumer behavior is greater than the t-table of 2,040 >2,003 with the sense that consumer behavior variables positively affect purchasing decisions.